The Novel Linearly and Circularly Polarized Dipole-like Antennas Fed by the Rectangular Waveguide - D. A. Buhtiyarov; A. P. Gorbachev; V. V. Atuchin (Innovations in Science and Technology Vol. 8, 2022)
The two kinds of the modified waveguide-fed dipole-like antennas are proposed and designed using the induced electro-motive force (EMF) method. To excite both the linearly polarized antenna’s arms, the two equal in magnitude and out-of-phase excitations are created using the standard rectangular waveguide. Since the area around the radiating arms is free of any conductors (exception for a finite ground plane), the antennas’ radiations are of high polarization purity. Additionally, the novel circularly polarized waveguide-fed crossed dipole-like radiator is proposed, in which the split-coaxial balance unit is used. Both the stand-alone antennas operating near 1.7 GHz and 2.0 GHz were fabricated and tested to verify the design validity. The results show that the proposed antennas have an impedance bandwidth of 1.68–1.71 GHz (fractional frequency band 0.03 GHz, relative band 1.8%) for the linearly polarized radiation, and the corresponding quantities 1.95–2.05 GHz (0.1 GHz, 5%) with 3 dB axial ratio bandwidth of 1.98 – 2.02 GHz (0.04 GHz, 2%) for the circularly polarized one. Both the far-field patterns and the reflection coefficient’s level show good agreement with the simulation-derived parameters. Such the antennas are acceptable for using as a building block in the linearly polarized waveguide-fed E- and H-arrayed assemblies as well as the circularly polarized stand-alone radiators. The proposed approach paves a way for next generation of the waveguide-fed antennas.